Maize initial growth with the inoculation of plant growth-promoting bacteria (PGPB) under different soil acidity levels - Inagaki, Adriano Mitio; Guimarães, Vandeir Francisco; Lana, Maria do Carmo; Klein, Jeferson; da Costa, Andréia Cristina Peres Rodrigues; Rodrigues, Luan Fernando Ormond Sobreira [UNESP]; Rampim, Leandro (My University, 2015)
The effects of plant growth promoting bacteria (PGPB) on the initial growth and leaf gas exchange parameters of maize plants (Zea mays L.), and bacterial population of the root and non-rhizosphere soil were investigated under different soil acidity levels. Maize plants were grown in 13-dm3 pots filled with clayey Rhodic Hapludox in a greenhouse. Treatments were arranged in a randomized block design in a 3 × 4 factorial: three soil acidity levels [pH in 0.01mol L-1 CaCl2 solution of 4.5; 5.0 and 5.5] and four seed inoculation treatments [control (non-inoculated); inoculation with Azospirillum brasilense strain AbV5; inoculation with Herbaspirillum seropedicae strain SMR1; and inoculation with two bacteria strains (A. brasiliense + H. seropedicae)]. Seeds inoculation with two PGPB strains (AbV5 and SMR1) improved the leaf area (14%), stem diameter (7%), relative chlorophyll content (14%), but had no effect on dry matter yield of maize plants, even with the changes of soil acidity levels. At 15 days after sowing, the inoculation of A. brasilense resulted in increased of diazotrophic bacteria density in the soil (15%). At 41 days after sowing, the inoculation of PGPB strains (AbV5 and SMR1) resulted in increased of diazotrophic bacteria density in the maize roots (13%). Seed inoculation with H. seropedicae enhances the nitrogen concentration in the leaf tissue of maize (12%) under soil acidity conditions and without the nitrogen supply, indicating increase in the biological nitrogen fixation. Inoculation of PGPB in acidic sandy soil (4.5 to 5.0 pH) resulted in higher phosphorus concentration in the leaf tissue of maize, indicating increase of phosphorus solubilization promoted by the diazotrophic bacteria. Leaf CO2 assimilation rate was not affected by the maize seed inoculation with PGPB. Soil acidity resulted in the reduction of stomatal conductance (-25%), leaf CO2 assimilation rate (-14%), leaf transpiration rate (-21%) and water use efficiency (-6%) of maize plants. The NFb Lactate (selective for A. brasilense) and NFb Malate (selective for H. seropedicae) culture media were not effective in differentiating of the two diazotrophic species studied and Herbaspirillum seropedicae, for both the root and soil samples.
Keywords: Azospirillum brasilense; Gas exchange; Herbaspirillum seropedicae; Soil pH; Zea mays